Examining the Direct and Indirect Impacts of E-Supply Chain Implementation on Performance: A Collaborative Approach - Sheyadi, Anwar Al; Shaukat, Muhammad Rehan (International Journal of Supply Chain Management, 2023)
The paper examines both the direct and indirect impact of implementing E-Supply Chain Management (E-SC) practices on performance of Omani manufacturing firms.  A Structural Equation Modelling analysis was conducted based on a large scale survey applied to 108 manufacturing firms. Results of the research revealed that E-SC practices had a direct positive effect on both business and operational performance, where their direct effects on operational performance was stronger than their effect on business performance.  The results also showed that while the indirect effect of E-SC on operational performance was partially supported, a full indirect effect between E-SC and business performance was found.  Our findings imply that although a substitutive implementation of various types of E-SC can lead to marginal positive performance outcomes, achieving substantial performance outcomes might require more collaborative and highly coordinated approach of implementing these practices.  Several other theoretical and practical insights are provided by the findings of this paper on understanding the potential benefits of the direct and indirect implementation of E-SC practices.